PRICE SETTING IN LITHUANIA: MORE EVIDENCE FROM THE SURVEY OF FIRMS - Virbickas, Ernestas (Ekonomika, 2011)
The article examines price setting in Lithuania, based on the ad hoc survey “On Price and Wage Setting” of the Bank of Lithuania. The study extends the survey data analysis presented in Virbickas (2009). The article points to the incidence of both time-dependent and state-dependent price reviewing policies used by the firms under study, though the price reviewing practices appear to be somewhat tilted to the state-dependent pricing. Analysis provides evidence on the reasons for the upward and downward stickiness of prices. Delayed price adjustment is found to be related to the price adjustment rather than the price reviewing stage. The most momentous explanations for not adjusting prices upwards or downwards rest on the cost-based pricing and the explicit contracts. The study finds an asymmetric influence of some of the price factors. In particular, the cost factors are found to be decisive in invoking a price increase rather than a price decrease.